Animal behavior : - Alcock, John (Sinauer Publishers, 2001)
This new edition of Animal Behavior has once again been thoroughly rewritten with coverage of much recent work in animal behavior, while retaining the many successful features of previous editions. The writing style is clear and engaging; the book is well illustrated with many new photographs; and the discussion questions are embedded in the text to encourage the development of problem-solving skills of students. This now-classic text continues to offer a balanced treatment of the underlying mechanisms and evolutionary bases of behavior with a focus on the importance of evolutionary theory for the unification of the different behavioral disciplines.